PERANCANGAN FASILITAS KERJA YANG ERGONOMIS PADA PROSES PEMOTONGAN MATERIAL DI DEPARTEMEN STORE DI PT PEGAUNIHAN TECNOLOGY INDONESIA - Sinaga, Mikael; Zetli, Sri (LPPM Universitas Putera Batam, 2025)
This study is a study conducted on the Department Store operator at PT Pegaunihan Tecnology Indonesia, in the manual handling work process workers have a high risk of mulculoskeletal Disorders (MSDs). The study was conducted by observation and distributing questionnaires to workers, the results of the Nordyc Body Map (NBM) questionnaire showed a total of 24 workers complained of upper neck body parts, stiff neck with a percentage of over 90% of workers feeling these complaints. Furthermore, calculations with Rapid Entire Body Assessment (REBA) resulted in 3 workers with the highest risk with a high risk category. From this situation, improvements need to be made. To make improvements, anthropometric data is used, the body dimension data needed in the design is PTD (Front Arm Length), TSB (Standing Elbow Height) and Arm Span. After the calculation, the dimensions of the table were obtained with a width of 70 cm, a length of 110 cm and a height of 103 cm, the complaint value decreased from initially high risk to low risk.